PERANCANGAN DAN IMPLEMENTASI WEBSITE SEKOLAH DASAR NEGERI 1 KOTA GURING SEBAGAI MEDIA INFORMASI DAN KOMUNIKASI - Meizary, Ary; Rika Lestari, Winda; N, Nisar (Jurnal Pengabdian Masyarakat Tapis Berseri (JPMTB), 2025)
The rapid development of technology has opened many potential resources, one of which is the use of websites. A website is essential for increasing the visibility, reputation, and credibility of an organization. A school website is one type of organizational site that has a significant impact on the sustainability of a school. In today’s digital era, the use of information technology in education is becoming increasingly important, including at the elementary school level. Schools in Lampung Province need to have web-based information systems to support transparency, efficiency, and easy access to data for teachers, students, and parents. However, many elementary schools in Lampung still do not have an optimal information system, including SD Negeri 1 Kota Guring. The main problem faced is the absence of an official school website that provides information about the school profile, academic activities, and other important data. This community service activity aims to design and develop a school website using Google Sites as a digital information medium. The website is expected to facilitate access to academic and non-academic information for students, parents, and the wider community. The results show that SD Negeri 1 Kota Guring now has an accessible website for all stakeholders, which helps improve information transparency and strengthens the school’s professional image.